Regulation of ADP-ribosyltransferase activity by ART domain dimerization in PARP15 - Ebenwaldner, Carmen ; 0000-0002-7919-2994; García Saura, Antonio Ginés; Ekström, Simon; Bernfur, Katja; Moche, Martin; Logan, Derek T. ; 0000-0002-0098-8560; Cohen, Michael S.; Schüler, Herwig ; 0000-0003-4059-3501 (Nature Communications, 2025)
PARP15 is a mono-ADP-ribosyltransferase that targets an unknown set of proteins as well as RNA. Its evolutionary relationship with PARP14 suggests roles in antiviral defence; its localization to stress granules points to functions in the regulation of translation. Here we show that the transferase domain of PARP15 dimerizes in solution; the formation of dimers is a prerequisite for catalytic activity and monomeric mutant variants of the domain are inactive. In cells, dimer-disrupting mutations abrogate catalytic activity and alter the subcellular localization of the full-length protein. Using biophysical methods, including X-ray crystallography and HDX-MS, we provide evidence for a regulatory mechanism by which dimerization enables correct target engagement rather than NAD+ co-substrate binding, and by which the two protomers of the dimer operate independently of one another. Together, our results uncover a regulatory mechanism in a PARP family enzyme.
Publisher Copyright: © The Author(s) 2025.